Regulasi Hukum Merek Terhadap Merek Terkenal - Rika Novalina; Nia Nopianti; Johansyah; Fadli Rahman Wahidi (Lex Stricta : Jurnal Ilmu Hukum, 2025)
This research is an intensive, detailed, and in-depth literature study. The data collection method used in this study is the applicable regulations, and legal analysis is one of the useful research methods for future legal knowledge needs. To analyze the files from the search results, primary and secondary data can be processed and then analyzed qualitatively. Subsequently, a review was conducted, and the essence was obtained. The legal regulation of the trademark system adopted in Indonesia is the “first-to-file” system, meaning that the first applicant to file will be protected. However, pursuant to Article 21 of Law No. 20 of 2016 on Trademarks and Geographical Indications, the applicant for trademark registration must act in good faith. Therefore, the first applicant whose rights are protected is the one who acts in good faith.